The Influence of the Problem Based Learning Model Assisted by the Firing Line on Critical Thingking Skills in the Science Subject of 4th Grade Emlementary School Students - Hasanah, Fina Nessa; Mayarni, Mayarni (Pendidikan Kimia Unimus, 2024)
The research at this time aims to analyze the ability of each student in the type of critical thinking by using a problem-based learning model supported by the firing line. The research method used is a quantitative research approach with a pretest-posttest research design of non-equivalent control group design. There are 31 students who are declared as the experimental class while for 31 students who will be the control class will be randomly selected. In this study using an instrument containing 12 essay questions. The final result of this study shows the paired-sample t-test analysis that the significance value (two-tailed) is 0.000, which is less than 0.05. In addition, the N-gain test displays the average of the N-gain for the experimental class which is 0.7490 can be categorized as